Analisis Literasi Digital Mahasiswa dalam Menyaring Informasi Keagamaan pada Era Revolusi Industri 4.0: An Analysis of Digital Literacy Among University Students in FilteringReligious Information in the Era of the Fourth Industrial Revolution - Rizkia Dwi Agistia; Arjuna Samudra; Eyi Junita; Julia Hardiana; Dinda Firda; Muji Agus Sofyandi (Al-Faiza : Journal of Islamic Education Studies, 2026)
The rapid advancement of information technology in the Industrial Revolution 4.0 era has significantly changed the way people access, obtain, and disseminate information, including religious information. Ease of access to digital platforms provides significant opportunities for religious learning, but at the same time, it also increases the spread of hoaxes, misinformation, hate speech, and religious content that contradicts the principles of religious moderation. This research used a qualitative approach with a literature review method. Data were collected from academic books, scientific journal articles, previous research results, and official documents related to digital literacy, digital media, and religious information. Data analysis was conducted using content analysis techniques, which include data reduction, data presentation, interpretation, and drawing conclusions. The results indicate that students' digital literacy is influenced by critical thinking skills, competence in evaluating the credibility of information sources, a culture of literacy, and responsible use of digital media. Strengthening digital literacy through higher education, curriculum integration, and religious moderation education are considered effective strategies for developing students who are able to wisely filter religious information and prevent the spread of misleading information in the digital environment.